Transmission Based Precaution Practices among Nurses in Edo State, Nigeria during COVID-19 Pandemic - Afemikhe, Juliana A.; Esewe, Roselyd E.; Enuku, Christie A. (African Journal of Reproductive Health, 2020)
The novel covid-19 pandemic is a highly infectious disease without known specific treatment and vaccine. Transmission based precautions are important in the fight against the virus. This study investigated the level of transmission-based precautions practiced, the predictors of correct practices, and the challenges experienced by nurses in public health facilities in Edo State during the outbreak of the Covid-19 pandemic. The study employed a descriptive cross-sectional survey to elicit responses from 367 front line nurses using a Google online questionnaire. Data analysis involved descriptive statistics and logistic regression analysis. The majority 314(85.6%) of the respondents maintained a good level of transmission-based precautions practice. Hand hygiene was performed by 327(89.1%) of the respondents. Academic qualification was a significant predictor of good practice in favour of respondents with a degree in nursing. Challenges identified were lack of financial motivation, fear of infecting family members and fear of contracting the virus (93.5%). It was concluded that nurses in Edo State Nigeria have good transmission based practices in relation to covid-19 however efforts should be made to ensure 100% compliance and sustain practices
Keywords: ACE: Reproductive Health Innovation; University of Benin; Nigeria; CERHI; Timothy A. Ehwarieme; Edo State; Transmission based precautions; Practice; Health facilities; Covid-19